Illicit Trade in Nuclear Black Market and Present-Day Challenges - Ms. Hajira Asaf Khan (CISS Insight Journal, 2015)
The proliferation of nuclear weapons has long been a pressing concern for the international community which has brought together a majority of states in efforts to retard the acquisition of nuclear weapons capability by more states. However, these efforts have not always been successful. At the time of entry into force of the Treaty on non-Proliferation of Nuclear Weapons (NPT), five states namely the US, the then USSR, Britain, France and China possessed nuclear weapons. These countries today are recognized as the de jure or “normal” nuclear weapons states, while India, Pakistan, North-Korea and Israel do not enjoy the legitimate status and are considered de facto nuclear powers because of their known nuclear weapon capabilities.In addition to proliferation of nuclear weapons to states, the possibility of non-state actors acquiring these capabilities has added to the concern in recent years. The rise of extremist organizations like Al-Qaeda and the Islamic State (IS), and their open admission of nuclear aspirations, have injected new life into the efforts to prevent non-state actors from getting their hands on this technology. Knowledge of nuclear science and access to technology has become available to more and more people due to increasing accessibility of knowledge in the last few decades. However, making of a nuclear weapon remains a highly specialized job. Development of nuclear weapons is reliant on special materials, precision engineering and industrial capabilities that not many states can boast of, let alone rogue organizations like the IS.